The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1016/j.physleta.2003.10.009
|View full text |Cite
|
Sign up to set email alerts
|

On phase transition and vortex stability in the generalized XY models

Abstract: We study a recent generalization proposed for the XY model in two and three dimensions. Using both, the continuum limit and discrete lattice, we obtained the vortex configuration and shown that out-of-plane vortex solutions are deeply jeopardized whenever the parameter of generalization, L, is increased. The critical temperature for such models is calculated using the self consistent harmonic approximation. In both, two-and three-dimensional cases, such a temperature decreases with raising L. Our results are a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
1
12
0
3
Order By: Relevance
“…In turn, different techniques, such as self-consistent harmonic approximation (SCHA) and Monte Carlo (MC) simulation, have been used to study this transition when q > 1. It was found that the BKT critical temperature decreases as q increases and this model was proved to be the same universality class as the usual XY model [7,9,10,8]. Once the BKT transition appears, the vortex pair density starts to grow simultaneously.…”
Section: Introductionmentioning
confidence: 76%
“…In turn, different techniques, such as self-consistent harmonic approximation (SCHA) and Monte Carlo (MC) simulation, have been used to study this transition when q > 1. It was found that the BKT critical temperature decreases as q increases and this model was proved to be the same universality class as the usual XY model [7,9,10,8]. Once the BKT transition appears, the vortex pair density starts to grow simultaneously.…”
Section: Introductionmentioning
confidence: 76%
“…In some recent papers [8,24,25,27] a class of generalized XY models was introduced and studied. These models are ferromagnetic and, in the simplest case, restricted to a nearestneighbour XY -type interaction.…”
Section: Introductionmentioning
confidence: 99%
“…When q is small, the first-order phase transition phenomenon is not obvious, or even there may be no first-order phenomenon. When q is large enough, such as q > 6, the first-order phase transition becomes more and more obvious [14][15][16][17]. We know that the BKT phase transition is caused by the release of vortex antivortex pairs at the critical temperature point.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…As shown in Figure 4, the vortex density increases almost precipitously with the increase of q. These two kinds of phase transitions occur at almost the same temperature point, so it is difficult to accurately judge the phase transition properties [15,16]. How to accurately determine the first-order phase transition temperature may be an interesting research in the future.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation